The Analysis Errors Of Students In Solving Problems On The Material Of Temperature and Heat - doni doni; Stepanus Sahala Sitompuls; Firdaus (Jurnal Pendidikan Fisika Undiksha, 2023)
This study aims to find out the errors of students in solving problems on the material of temperature and heat. This research method is a descriptive survey method. Using porposive sampling, the subjects in this study were class XI IPA 2 for the academic year 2021/2022 with 32 test participants. The research instrument is an essay test with 4 questions and interviews. From the results of the analysis it can be concluded that the ability of students in solving temperature and heat material questions is categorized as low. The students' errors that were examined were errors in unresponsive questions, errors in writing concepts, errors in using data, errors in writing formulas, errors in entering numbers, counting errors, and mathematical errors.